Public perception of the management of medical B3 waste and wastewater at health centers in Rejang Lebong Regency - Anggreni Dewi; Budihardjo Mochamad Arief; Muhammad Fuad (E3S Web of Conferences)
Final processing of medical B3 waste using an improper incinerator can produce GHG emissions and release pollutants into the air. Disposal of wastewater that does not meet quality standards or is not managed into the environment can pollute surface water and groundwater. This study examines public perceptions of the management of medical B3 waste and wastewater at health centers in Rejang Lebong Regency. The results of questionnaire data processing from 105 respondents stated that the public considered the health centers to have carried out good medical B3 waste management of 79.62%, and wastewater management of 72.76%. Efforts to improve the performance of medical B3 waste and wastewater management, namely: (a) increasing efforts to reduce, reuse and recycle, such as reusing hemodialysis jerrycans, recycling infusion bottles and PPE, and composting of sludge from IPAL processing; (b) increasing efforts to sort medical B3 waste; (c) adjusting the design of the B3 waste TPS and providing cold storage; (d) providing and repairing IPAL; (e) increasing the capacity of waste management officer; and (f) increasing the allocation of costs for environmental management and monitoring. Implementing these efforts can minimize the impact on health and the environment and help achieve SDGs 6 and 12.